World Eaters : How Venture Capital is Cannibalizing the Economy - Bracy, Catherine (New York : Dutton, 2025)
"An urgent and illuminating insider/outsider perspective that offers a window into how the most pernicious aspects of the venture capital ethos is reaching all areas of our lives, into everything from healthcare to food to entertainment to the labor market, and leaving a trail destruction in their wake"--
The methodology: how venture capitalists think -- The founders: how VC undermines entrepreneurship -- Venture capital and labor: how the gig economy has upended the job market -- Venture capital and housing: capsizing the American dream -- The pathbreakers: can venture capital be done differently? -- The changemakers: how to scale what works.
Includes bibliographical references (pages [233]-252) and index.
Keywords: Venture capital; Economics; Food industry and trade